Pengaruh Model Pembelajaran Picture and Picture Terhadap Minat Belajar PAK Siswa Kelas VII SMP Negeri 2 DolokSanggul Tahun Pembelajaran 2019/2020 - Elfira Silaen (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
The purpose of this study was to determine the effect of Picture and Picture Learning Model on students’ interest in Learning Christian Religion Education of Grade VII in SMP Negeri 2 DolokSanggul Academic Year 2019/2020.The method used in this research is inferential statistical method. The population was all grade VII students of SMP Negeri 2 DolokSanggul Academic Year 2019/2020 with a total of 281 people and a sample of 32 people. Data were collected with a closed questionnaire of 35 items.The results of data analysis showed that the Picture and Picture Learning Model had a positive and significant effect on students’ interest in Learning Christian Religion Education of Grade VII in SMP Negeri 2 DolokSanggul Academic Year 2019/2020 with data analysis as follows: 1. Test requirements for analysis: a) A positive relationship test obtained rxy = 0.745 rtable = 0.349; b) Significant relationship test obtained tcount = 6.109 ttable = 1.697 between variable X with variable Y. 2. Influence test: a) Regression equation test obtained a regression equation with a regression determination coefficient r ^ 2 = 55, 5% and Fcount Ftable = 1.92 1.62, thus Ha and H0 were rejected. There is a positive and significant effect of the Picture and Picture Learning Model on students’ interest in Learning Christian Religion Education of Grade VII in SMP Negeri 2 DolokSanggul Academic Year 2019/2020. Keywords: Picture and picture Learning Model, Students’ Learning Interest, Christian Religion Education